The Ontological Argument from the Perspective of Allama Muhammad Taqi Ja'fari and Allama Abdullah Jawadi Amoli: برھان وجودی علامہ محمد تقی جعفری اور علامہ عبداللہ جوادی آملی کے نقطہ نظر سے - Ali, Mukhtiar; Rezapour, Prof. Dr. Muhammad (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
The Ontological Argument is one of the fundamental arguments in theology that employs a rational and demonstrative method based on the concept of "the greatest conceivable being" or "the most perfect being beyond which no greater perfection can be conceived" to prove the existence of God Almighty. Among the rational arguments for the existence of God, the Ontological Argument has been the most controversial and has sparked serious discussions in both the Western and Eastern philosophical traditions. Since its initial formulation, it has had staunch proponents and critics, indicating its significance among both Western and Eastern thinkers.In the Eastern intellectual tradition, Allama Muhammad Taqi Ja'fari and Allama Abdullah Jawadi Amoli are two prominent Islamic scholars who have critically examined this argument. The present research aims to analyze their views using a descriptive-analytical method. The findings indicate that these two Islamic philosophers hold divergent perspectives on the Ontological Argument. Allama Ja'fari considers the argument to have both rational and scriptural foundations and accepts it as a valid proof for the existence of God. In contrast, Allama Jawadi Amoli, based on the distinction between two types of predication (primary essential predication and common technical predication), raises fundamental criticisms. He argues that the Ontological Argument mistakenly conflates concept and instantiation and misinterprets primary essential predication, thereby rejecting it as a valid proof for God's existence.